2020
DOI: 10.5194/acp-20-3079-2020
|View full text |Cite
|
Sign up to set email alerts
|

Surface temperature response to regional black carbon emissions: do location and magnitude matter?

Abstract: Abstract. Aerosol radiative forcing can influence climate both locally and far outside the emission region. Here we investigate black carbon (BC) aerosols emitted in four major emission areas and evaluate the importance of emission location and magnitude as well as the concept of the absolute regional temperature-change potentials (ARTP). We perform simulations with a climate model (NorESM) with a fully coupled ocean and with fixed sea surface temperatures. BC emissions for year 2000 are increased by factors o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…This highlights the complex response of the nonlinear climate system to not only the magnitude but also the spatial pattern of aerosols. This nding is broadly consistent with previous E p based, idealized model simulations [8][9][10][11][12][13] , although our results are based on realistic E c emissions. For climate policy considerations and international negotiations, a climate change attribution assessment based on fully coupled model simulations driven by realistic, regionally detailed emissions is important.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This highlights the complex response of the nonlinear climate system to not only the magnitude but also the spatial pattern of aerosols. This nding is broadly consistent with previous E p based, idealized model simulations [8][9][10][11][12][13] , although our results are based on realistic E c emissions. For climate policy considerations and international negotiations, a climate change attribution assessment based on fully coupled model simulations driven by realistic, regionally detailed emissions is important.…”
Section: Discussionsupporting
confidence: 92%
“…For aerosols, which are short-lived, the spatial distribution of consumption associated emissions determines the distribution of their atmospheric loadings and thus exerts spatially inhomogeneous forcing 6,7 to the nonlinear climate system. Emerging evidence has suggested strong nonlinearity in the climate response to the magnitude 8,9 and location [10][11][12][13] of aerosols ─ for example, one study suggests that a given amount of aerosol emissions released in Western Europe cause 14 times as much global average cooling as when emitted in India 11 . These studies are solely based on idealized model experiments by scaling the emissions with an arbitrary factor or by putting the same amount of emissions to different locations.…”
mentioning
confidence: 99%
“…The 43.2 Gg of BC emissions were responsible for 5.8 millikelvin (mK) of Arctic warming (13.4 mK of warming per 100 Gg emitted). This result is comparable to that from Sand et al (2020), in which 10 mK of warming per 100 Gg emitted was modeled in a scenario where baseline European BC emissions were perturbed by a factor of 10. Snow and ice deposition were responsible for 64% of warming influence from BC.…”
Section: Resultssupporting
confidence: 86%
“…The regional temperature response approach developed by Sand et al (2015) does have some limitations. In particular, the Arctic temperature responses were developed using very large emissions changes in order to create a signal, and recent research has suggested nonlinearities with the size of the emissions change (Sand et al, 2020; Yang et al, 2019), with Arctic temperature responses generally being larger per ton of emission change for smaller emission changes. However, it remains the best approach available for examining the Arctic temperature impacts of aerosol emissions perturbations, as direct modeling would be computationally prohibitive and not sufficiently sensitive for perturbations of the magnitude examined in this manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in 2004, Johnson et al [49] demonstrated the warming effect of absorbing particles within the mixing layer. Recently, Sand et al [50] found a non-linear relationship between emissions rate and temperature variation at ground level: the higher is the BC emission rate, the lower is the air temperature sensitivity because the convection in the lower atmospheric levels promote convection and turbulent motion moving BC from the surface to the mixing layer top. In other words, the net motion results in enhancing aerosol upward vertical transport.…”
Section: Correlations Between the Atmospheric Turbidity And Surface Air Temperaturementioning
confidence: 99%